Comparison of Various Formulas (Hadlock’s I and II, Merz, Shepard, Campbell, Wilkin’s) to Calculate Birth Weight by Antenatal Ultrasound - R Mahesh Anirudh; T Shriram; CS Prabhu; P Ramya (Journal of Pharmacy and Bioallied Sciences)
Background: Accurate fetal weight estimation is crucial in obstetric care, aiding in the management of intrauterine growth restriction, macrosomia, and perinatal decision-making. Aim: To compare the accuracy of different sonographic formulas for estimating fetal birth weight and determine the most reliable formula. Materials and Methods: A prospective comparative study was conducted in the Department of Radiology at Aarupadai Veedu Medical College and Hospital, Puducherry. A total of 110 pregnant women with gestational ages above 37 weeks were enrolled. Ultrasound examinations were performed using the Mindray DC 80 scanner. Estimated fetal weights using Hadlock’s I and II, Merz, Shepard, Campbell, and Wilkin’s formulas were compared with actual birth weights. Statistical analysis included paired t-tests, ANOVA, and post hoc Tukey’s test, with significance set at P < 0.05. Results: Hadlock I and III demonstrated the highest accuracy, particularly in the 2.6–3.0 kg range. Merz and Wilkin’s formulas overestimated higher birth weights, while the Shepard formula consistently underestimated fetal weight. Conclusion: Hadlock I and III are the most reliable formulas for fetal weight estimation. Selection of an appropriate formula is essential for clinical accuracy.